Pengaruh Influencer, Literasi Keuangan Dan Ekspektasi Return Terhadap Minat Investasi Cryptocurrency Pada Mahasiswa Universitas Islam Malang - Al Majdi, Raihan Zaki; Wahono, Budi; Bastomi, Mohamad (UNIVERSITAS ISLAM MALANG, 2025)
Abstract Investment in digital assets such as cryptocurrency has grown rapidly, particularly among younger generations. This study aims to analyze the influence of influencers, financial literacy, and return expectations on the interest in cryptocurrency investment among students of the Islamic University of Malang. A quantitative approach was employed using a survey method with 130 respondents selected through purposive sampling. Data were collected via questionnaires and analyzed using multiple linear regression with SPSS software. The results show that simultaneously, influencers, financial literacy, and return expectations have a significant effect on investment interest in cryptocurrency. Individually, each variable also has a positive and significant impact. Influencers provide encouragement through informative and relevant content, financial literacy helps students understand the risks and potential of digital assets, while return expectations motivate interest based on the potential for high profits. The study concludes that these three factors play a crucial role in shaping student investment interest and recommends enhancing financial education and monitoring information on social media to support more informed investment decisions. Keywords: Influencer, Financial Literacy, Return Expectations, Investment Interest, Cryptocurrency